Hopf Bifurcation and Stability Analysis of a Congestion Control Model with Delay in Wireless Access Network - Wen-bo Zhao; Xiao-ke Sun; Huicheng Wang (Abstract and Applied Analysis)
We drive a scalar delay differential system to model the congestion of a wireless access network setting. The Hopf bifurcation of this system is investigated using the control and bifurcation theory; it is proved that there exists a critical value of delay for the stability. When the delay value passes through the critical value, the system loses its stability and a Hopf bifurcation occurs. Furthermore, the direction and stability of the bifurcating periodic solutions are derived by applying the normal form theory and the center manifold theorem. Finally, some examples and numerical simulations are presented to show the feasibility of the theoretical results.